INVESTIGATING BEYOND THE LABEL OF â€œHALALAN-THAYYIBANâ€: THE HALAL GUARANTEE SYSTEM IN LOCAL RESTAURANT - Pusparini, Martini Dwi; Setiaji, Herman (UNISSULA, 2019)
For Muslims, Islamic business ethics is an absolute thing to be applied in business activities. Yogyakartais a province that consists of Muslims in majority, having potentials of requiring halal products. This research aimed at finding the implementation of Islamic business ethics in the halal and thayyib guarantee system on the offered products in order to discover the implementation of the halal labeling applied. This research was a descriptiveexplorative study using qualitative approach. The research was conducted by interviewing the managers and cook of the restaurant using in-depth interview. It was found out from the results of the study that the Ayam Penyet Surabaya Restaurant has carried out good implementation of Islamic business. In addition, regarding to the halal and thayyib guarantee system, the performance in the fields of halal organization, procurement, processing, transparency, and standardization towards the Standard Operating Procedure (SOP) and Halal Guarantee System (SJH) were under control and evaluation. Both the control and the evaluation were presented in the form of halal, proportional, and secure presentation in accordance with the company standards which are based on five halal aspects in regards to product and use of materials. Their implementation was thoroughly and generally conducted in a good and structured way. The limitation of the research was the lack of sample observed, as the result only applied at one object only. For future research, the researchers should apply more than one object of research.